Review of the Interventions that Improve the Perceived utility of Learning by Students - Sánchez-Rosas, Javier (2019)
Currently, educators face the challenge of making students consider useful what they teach in class. According to the expectation- value of motivation theory, the perceived usefulness is considered flexible in the face of external interventions. Even though a recent growing body of research has assessed the effectiveness of such interventions, there are no known publications that have reviewed the quantity, characteristics, concepts, correlates, and functioning of the examined interventions. To this end, the intention of this study was to describe the interventions that promote the usefulness perceived by the students. A non-systematic bibliographical review was carried out, producing ad hoc analysis criteria. Twelve interventions were identified, all based on the theoretical expectation-value model. The type, quantity and duration of the activities are diverse, consisting of asking students to make connections between the topics learned in class and their daily lives. Furthermore, the frequency of those connections is the mechanism through which interventions have an effect on learning. This review provides a variety of resources to the practice and research on education in order to produce changes in the perceived usefulness and improve the student’s focus and performance.